التحكم الصوتي للإنارة عبر البلوتوث - مسعودة, مفتاح; مروة, عزوز (جامعة الشهيد حمه لخضر الوادي, 2023)
This memory is intended to show how to achieve lighting control using voice and bluetooth technology. The circuit consists of the bluetooth module, relay module, controller and lamp. The bluetooth module is connected to the control unit and the lamp with the relay module is connected. The controller is programmed using the appropriate development software and sets the ports and parameters needed to initialize the bluetooth module and read the audio signals. The audio signals are processed using the appropriate programming libraries and specifying the required voice commands. Based on voice commands, the lamp light is turned on and off. The system is tested by downloading the software to the console, confirming that the components are connected correctly, and sending voice commands from the transmitting device. "تهدف هذه المذكرة إلى توضيح كيفية تحقيق التحكم في الإضاءة باستخدام الصوت وتقنية البلوتوث. تتكون الدارة من وحدة البلوتوث ووحدة الترحيل ووحدة التحكم ومصباح. يتم توصيل وحدة البلوتوث بالوحدة التحكم والمصباح مع توصيل وحدة الترحيل. يتم برمجة الوحدة التحكم باستخدام برنامج التطوير المناسب وتعيين المنافذ والمعلمات اللازمة لتهيئة وحدة البلوتوث وقراءة الإشارات الصوتية. يتم معالجة الإشارات الصوتية باستخدام مكتبات البرمجة المناسبة وتحديد الأوامر الصوتية المطلوبة. بنا ًء على الأوامر الصوتية، يتم التحكم في تشغيل وايقاف تشغيل المصباح. يتم اختبار النظام بتنزيل البرنامج على الوحدة التحكم وتأكيد توصيل المكونات بشكل صحيح وارسال الأوامر الصوتية من الجهاز المرسل."
مذكرة ماستر اتصالات Des thèses télécominication
Keywords: Control voice, Bluetooth, Arduino, Relay, Programming, Smart home automation, Application, Module Bluetooth HC-05; الاوامر الصوتية، البلوتوث، الاردوينو، الترحيل، البرمجة، أتمتة المنزل الذكي، التطبيق، وحدة البلوتوث HC-05